USAD: An Intelligent System for Slang and Abusive Text Detection in PERSO-Arabic-Scripted Urdu. (30th November 2020) - Haq, Nauman Ul; Ullah, Mohib; Khan, Rafiullah; Ahmad, Arshad; Almogren, Ahmad; Hayat, Bashir; Shafi, Bushra
Abstract : The use of slang, abusive, and offensive language has become common practice on social media. Even though social media companies have censorship polices for slang, abusive, vulgar, and offensive language, due to limited resources and research in the automatic detection of abusive language mechanisms other than English, this condemnable act is still practiced. This study proposes USAD (Urdu Slang and Abusive words Detection), a lexicon-based intelligent framework to detect abusive and slang words in Perso-Arabic-scripted Urdu Tweets. Furthermore, due to the nonavailability of the standard dataset, we also design and annotate a dataset of abusive, offensive, and slang word Perso-Arabic-scripted Urdu as our second significant contribution for future research. The results show that our proposed USAD model can identify 72.6% correctly as abusive or nonabusive Tweet. Additionally, we have also identified some key factors that can help the researchers improve their abusive language detection models.